A millennium of increasing diversity of ecosystems until the mid‐20th century. (22nd July 2022) - Martins, Inês S.; Dornelas, Maria; Vellend, Mark; Thomas, Chris D.
Abstract: Land‐use change is widely regarded as a simplifying and homogenising force in nature. In contrast, analysing global land‐use reconstructions from the 10th to 20th centuries, we found progressive increases in the number, evenness, and diversity of ecosystems (including human‐modified land‐use types) present across most of the Earth's land surface. Ecosystem diversity increased more rapidly after 1700 CE, then slowed or slightly declined (depending on the metric) following the mid‐20th century acceleration of human impacts. The results also reveal increasing spatial differentiation, rather than homogenisation, in both the presence‐absence and area‐coverage of different ecosystem types at sub‐global scales—at least, prior to the mid‐20th century. Nonetheless, geographic homogenization was revealed for a subset of analyses at a global scale, reflecting the now‐global presence of certain human‐modified ecosystem types. Our results suggest that, while human land‐use changes have caused declines in relatively undisturbed or "primary" ecosystem types, they have also driven increases in ecosystem diversity over the last millennium. Abstract : Land‐use change is widely regarded as a simplifying and homogenising force in nature. However, we found progressive increases in the number, evenness, and diversity of ecosystems present across most of the Earth's land surface until the mid‐20th century acceleration of human impacts. Nonetheless, geographic homogenization was revealed for a subset of analyses at a global scale, reflecting the now‐global presence of certain human‐modified ecosystem types. While the global story of biodiversity change involves the loss and decline of certain ecosystem types, the full story is more complex and interesting, involving gains and increases in other ecosystem types, and increased ecosystem diversity at most spatial and temporal scales.